2013
DOI: 10.1007/s40368-013-0042-7
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of spontaneous space closure after the extraction of first permanent molars

Abstract: Although only over half the patients had FPMs extracted at the "ideal time", this did not appear to influence successful positioning of the upper or lower SPM. More research is required to investigate and confirm which predictive parameters have a significant effect on post-extraction orthodontic development, especially in the lower arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 6 publications
0
62
1
12
Order By: Relevance
“…Teo et al [18] evaluated spontaneous space closure after FPM extraction in children aged 7–13 years. They classified space closure into five categories.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Teo et al [18] evaluated spontaneous space closure after FPM extraction in children aged 7–13 years. They classified space closure into five categories.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis was performed for the three studies [14, 16, 18] that reported space closure in both arches separately to compare the frequency of spontaneous space closure of the SPM in the maxilla with that in the mandible. Space closure was more likely to occur in the maxilla than in the mandible, but the difference was not statistically significant (odds ratio 2.06, 95% confidence interval 0.46–9.28; P  = 0.35).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations